Intraoperative Radiation for Breast Cancer with Intrabeam™: Factors Associated with Decreased Operative Times in Patients Having IORT for Breast Cancer - Valente, Stephanie A.; Fanning, Alicia; Stewart, Robyn A.; Grundfest, Sharon; Tendulkar, Rahul D.; Cherian, Sheen; Shah, Chirag; Tu, Chao; Yanda, Courtney; Radford, Diane; Al-Hilli, Zahraa; Grobmyer, Stephen R. (Frontiers in Oncology, 2017)
Introduction Intraoperative radiation with Intrabeam™ (IORT) for breast cancer is a newer technology recently implemented into the operating room (OR). This procedure requires time and coordination between the surgeon and radiation oncologist, who both perform their treatments in a single operative setting. We evaluated the surgeons at our center who perform IORT and their OR times to examine changes in OR times following implementation of this new surgical procedure. We hypothesized that IORT is a technique for which timing could be improved with the increasing number of cases performed. Methods A prospectively maintained IRB approved database was queried for OR times (incision and close) in patients who underwent breast conserving surgery (BCS), sentinel lymph node biopsy with and without IORT using the Intrabeam™ system at our institution from 2011 to 2015. The total OR times were compared for each surgeon individually and over-time. Next, the OR times of each surgeon were compared to each other. Continuous variables were summarized and then a prediction model was created using IORT time, OR time, surgeon, and number of cases performed. Results There were 5 surgeons performing IORT at our institution during this time period with a total of 96 cases performed. There was a significant difference observed in baseline surgeon specific OR time for BSC (p=0.03) as well as for BCS with IORT (p<0.05), attributable to surgeon experience. The average BCS times were faster than the BCS plus IORT procedure times for all surgeons. The overall mean OR time for the entire combined surgical and radiation procedure was 135.5 minutes. The most common applicator sizes used were the 3.5cm and 4cm, yielding an average 21minute IORT time. Applicator choice did not differ over time (p=0.189). After adjusting for IORT time and surgeon, the prediction model estimated that surgeons decreased the total BCS plus IORT OR time at a rate of -4.5 minutes per each additional 10 cases performed. Conclusion Surgeon experience and applicator size are related to operating room times for performing IORT for breast cancer. OR time for IORT in breast cancer treatment can be improved over time, even among experienced surgeons.